“PURIFIED” JAR WATER AT ROADSIDE TEA-STALLS IN DHAKA CITY PURE ENOUGH? - Chowdhury, Abhinandan; Hossain, Marzana; Hossain, Abir (International Journal of Research -GRANTHAALAYAH, 2018)
Due to high demand of pure water, in densely populated Dhaka city, “Jar” water business by private suppliers has hiked up in recent years. And currently negative reports on the purity of these jar water had been evident in social and print media. Therefore, checking microbial contamination in these jar water used in various road side tea stalls known as “Tongs”, was the aim of this study. In this study, a total of 55 jar water samples were collected from 30 tea stalls. Membrane filter was used to extract the bacteria, which were later grown on m-FC agar (for total coliform) and m-FC agar with Rosolic acid (for fecal coliform). A total of 190 bacterial colonies was isolated and from them 19 were E.aerogenes, 30 were Escherichia Coli, 3 were Klebsiella, 28 were Salmonella and 11 were Shigella. The presence of these five bacteria are the clear evidence of contamination in the supplied jar water at road-side tea stalls of Dhaka; indicating robust quality check for water purity is required by the supplier. Awareness amongst the customers and stall owners should be made for the safety of the stake holders from water-borne diseases.